Estimativa de consumo de sodio pela populacao brasileira, 2008-2009 - Sarno, Flavio (2013)
OBJECTIVE: To update estimates of sodium intake in Brazil. METHODS: We used data from the Brazilian Household Budget Survey of 2008-2009. Records of food purchases of households were converted into nutrients using food composition tables. Mean sodium availability per person per day and mean adjusted availability for a 2,000 kcal daily energy intake were calculated. The contribution of food groups to the total household sodium availability was calculated and compared to results estimated from the 2002-2003 Household Budget Survey. RESULTS: Mean daily sodium available for consumption in Brazilian households was 4.7 g per 2,000 kcal per day, thus still more than twice the recommended levels of intake for this nutrient. Although most of the sodium available for intake is derived from table salt or salt-based condiments (74.4%), the fraction derived from processed foods with added salt showed a strong linear increase with household income (12.3% of total sodium intake in the lower quintile of per capita income distribution and 27.0% in the upper quintile). There was a reduction in the contribution of salt and salt-based condiments (76.2% to 74.4%) and fresh or processed foods without added salt (6.6% to 4.8%) and an increase of processed foods with added salt (15.8% to 18.9%) and ready meals (1.4% to 1.6%), when compared to results estimated from the 2002-2003 Household Budget Survey. CONCLUSIONS: Sodium intake in Brazil remains at levels above the recommended maximum for this nutrient in all Brazilian macro regions and income strata. There was stability in the total household sodium availability, and an increase in the fraction from processed foods with addition of salt and ready meals, when comparing 2008-2009 with 2002-2003.